DESIGN AND IMPLEMENTATION OF A VOICE-CONTROL SYSTEM FOR COMPUTER APPLICATIONS USING PYTHON - Eenas Suwayd; Mahmuod saad (Surman Journal of Science and Technology, 2025)
Voice control systems have become an essential component of modern human–computer interaction. These systems enable users to operate computers and electronic devices through spoken commands using speech recognition and natural language processing technologies. This study investigates the design and implementation of a voice-controlled computer system using Python programming language. Several speech-processing libraries, including SpeechRecognition, PyAudio, and PyWhatKit, were utilized to develop a practical prototype capable of receiving voice commands and executing specific tasks such as searching and playing multimedia content on YouTube. The results demonstrate that voice-based applications can improve productivity, reduce human effort, minimize operational costs, and provide more convenient interaction with computers. The study also highlights the flexibility and simplicity of Python for developing speech-controlled applications and recommends extending such systems to support people with disabilities and more advanced intelligent applications.